2020
DOI: 10.1111/jfpp.15173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oven drying on bioactive compounds, antioxidant activity, and phenolic compounds of white and red‐skinned onion slices

Abstract: Moisture amounts of the white and red onions of the control group were determined to be 91.59% and 87.32%, respectively. The highest decrease in moisture content occurred within the red onion (7.14%) dried at 90°C. The total phenolic, total flavonoid contents, and antioxidant activity values of the white and red onions dried at both temperatures increased significantly compared to the control groups. The highest increase for total phenolic and total flavonoid contents were established for white and red onions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
0
12
4
Order By: Relevance
“…The lowest AA found in WH and GR samples dried at 60 °C might have probably resulted from the longer DT during FD. Additionally, other authors found that both drying temperature and drying time are the crucial factors that influence the antioxidant activity of leek [ 13 ] and other vegetables [ 55 , 56 ]. FD is considered to be one of the best but most expensive methods of food dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest AA found in WH and GR samples dried at 60 °C might have probably resulted from the longer DT during FD. Additionally, other authors found that both drying temperature and drying time are the crucial factors that influence the antioxidant activity of leek [ 13 ] and other vegetables [ 55 , 56 ]. FD is considered to be one of the best but most expensive methods of food dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…The influences of food processing on antioxidant capacities of onions were investigated as well, including drying (143,144), freezing (145), heating (41, 145), sautéing (38), and high-pressure processing (36). For instance, heating and freezing were found to reduce antioxidant activity of onion ( 145), while sautéing did not significantly change it (38).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This study recorded a quercetin content of 0.19±0.01 to 0.32 ±0.02. This varies with the result of Salamatullah et al(30) that recorded a quercetin content ranging from 0.89 ± 0.18 to 1.09 ± 0.06 in the control (un-dried) group, whereas they recorded the highest quercetin content in red onions oven-dried at 50 0 C. It also varies with the work of Jung-Ho et al(31) who recorded total quercetin glycosides varying from 16.10 to 103.93 mg/g DW extensively among three varieties of onions. Interestingly, Majid et al(29) found out in their research that sprouted onion powders contained more phytochemicals than raw onion powder which can be of importance in product development.…”
mentioning
confidence: 48%